2014
DOI: 10.2224/sbp.2014.42.5.731
|View full text |Cite
|
Sign up to set email alerts
|

The Mediating Role of Intrinsic Motivation on the Relationship Between Developmental Feedback and Employee Job Performance

Abstract: Although previous researchers have paid significant attention to the effect of feedback on employee behavioral outcomes, few have specifically examined the influence of developmental feedback on employee job performance. In this study we examined the influences of intrinsic motivation and social exchange on the relationship between developmental feedback and job performance. Participants were 202 supervisor-subordinate dyads from 12 enterprises in China. We found that developmental feedback had a significant p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
46
1
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(49 citation statements)
references
References 30 publications
1
46
1
1
Order By: Relevance
“…These variables included compensation, leadership, work discipline, work ability, and working conditions. The results of this analysis were contrary to the results of previous studies conducted by Dragos (2014), Guo, et al (2014), and Indrasari, et al (2018). The results of these studies stated that increasing employee motivation would directly affect performance improvement.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…These variables included compensation, leadership, work discipline, work ability, and working conditions. The results of this analysis were contrary to the results of previous studies conducted by Dragos (2014), Guo, et al (2014), and Indrasari, et al (2018). The results of these studies stated that increasing employee motivation would directly affect performance improvement.…”
Section: Discussioncontrasting
confidence: 99%
“…Inconsistent motivation causes obstacles to achieving individual goals in the organization and will cause organizational instability and have a very dangerous impact on the survival of the organization itself. Research on the positive relationship between motivation and performance was carried out by Guo, et al (2014). From the analysis of the research, a statement was produced that motivation and performance had a significant and positive relationship.…”
Section: Hypothesis Developmentmentioning
confidence: 99%
“…Good recruitment will be able to have a positive influence on increasing employee commitment, productivity and quality of work so that employee performance will significantly influence on their organization. Guo et al (2014) explain that the intensity of information on recruitment activities is significantly correlated with firm performance consistently. More intense recruitment activities carried out with a well programmed program will have positive impact on company performance and the individuals who contribute to the company are inseparable from the good recruitment program designed by the company.…”
Section: The Effect Of Recruitment On Employee Performancementioning
confidence: 85%
“…For example, individuals with a high power need perceive positive consequences when they are able to lead others and achieve dominance or influence over others. Guo, Liao, Liao and Zhang ( 2014 ) found that intrinsic motivation played a mediating role with evaluative or developmental feedback. Providing helpful and useful information without pressure for a particular outcome enabled employees to learn, develop, and improve their work.…”
Section: Feedback and Consequencesmentioning
confidence: 98%